(untitled) (MATEMATIKA, 2013)
The analysis of system behaviour near boundary of the stability domain requires the computation of Lyapunov quantities which determine a system behaviour in the neighbourhood of boundary This paper presents the computation of Lyapunov quantities and focal values of a homogeneous quartic polynomial system by using the Lyapunov-Poincare method where the polynomials are of degree four. The proposed two main theorems were proved to accomplish this goal. Keywords: Lyapunov quantities; focal values; Lyapunov-Poincare method; quartic polynomial system. 2010 Mathematics Subject Classification: 34C07; 34D08